Breastfeeding indicators trends in Brazil for three decades - Cristiano Siqueira Boccolini; Patricia de Moraes Mello Boccolini; Fernanda Ramos Monteiro; Sonia Isoyama Venâncio; Elsa Regina Justo Giugliani (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE Update breastfeeding indicators trend in Brazil for the last three decades, incorporating more up-to-date information from the National Health Survey. METHODS We used secondary data from national surveys with information on breastfeeding (1986, 1996, 2006, and 2013) to construct the time series of prevalence for the following indicators: exclusive breastfeeding in children under six months of age (EBF6m), breastfeeding in toddlers under 2 years of age (BF), continued breastfeeding at one year of age (BF1year), and continued breastfeeding at two years of age (BF2years). RESULTS The prevalence of EBF6m, BF, and BF1year increased until 2006 (rising from 4.7%, 37.4%, and 25.5% in 1986 to 37.1%, 56.3%, and 47.2% in 2006, respectively). For these three indicators, there was relative stabilization between 2006 and 2013 (36.6%, 52.1%, and 45.4%, respectively). The BF2years indicator had a distinct behavior - relatively stable prevalence, around 25% between 1986 and 2006, and a subsequent increase, reaching 31.8% in 2013. CONCLUSIONS The time series of breastfeeding indicators in Brazil shows an upward trend until 2006, stabilizing from that date onwards on three of the four indicators evaluated. This result, which can be considered as a warning sign, requires evaluation and revision of policies and programs to promote, protect and support breastfeeding, strengthening existing ones and proposing new strategies so that the prevalence of breastfeeding indicators returns to an upwards trend.